Interpréter l'art et la manière : que veut dire « tricher » dans un atelier de bijoutier ? - Brune Boyer-Pellerej (Images Re-Vues)
Based on the ethnography of Sophie Hanagarth’s workshop, a goldsmith-plastician, and on an experience in my own workshop, I will try to understand why the use of certain tools causes discomfort to the user. After watching Sophie for many hours, I was able to appreciate the application of her gestures and it was not without surprise that I heard her confess a few times: "Now... I cheat". Why does she use this expression when rolling a previously forged spindle-shaped steel bar, or when filing the curve of a bracelet with a file? Through the dual point of view of ethnography and auto-ethnography, it will be a question of what is at stake when it comes to certain technical choices. We will see that the study of the uses of technology informs us about different conceptions of the jeweller's profession and allows us to understand how this notion of cheating, mentioned furtively but repeatedly, raises the question of risk-taking in a jeweller's workshop.